Profil Penggunaan Antipsikotik Tipikal Pada Pasien Skizofrenia di Rumah Sakit Jiwa Daerah Sungai Bangkong Pontianak - ., Nova Claudia Sendika (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2019)
Schizophrenia is a psychiatric disorder caused by damage to the brain. Schizophrenia is treatedwith antipsychotics. The use of antipsychotics can cause side effects of extrapyramidal syndromein schizophrenic patients. This study aims to determine the antipsychotic drugs used anddetermine the percentage of patients with extrapyramidal reactions from the use of antipsychoticsin schizophrenics in Bangkong River Region Psychiatric Hospital Pontianak. This type ofresearch uses observational methods with cross sectional research design that is descriptive. Datacollection was carried out retrospectively from the patient's medical record. The study populationwas all inpatients in January-December 2018 who met the inclusion criteria. The number ofstudy subjects was 61 patients. The results of the study based on the characteristics ofschizophrenia patients showed 60.66% more male patients than women. The highest age groupof patients is in the adult age group of 18-40 years which is equal to 62.30%. The mostextrapyramidal symptoms were found in akathisia 34.42%, dystonia and tardive dyskinesia18.03%, and parkinsonism 29.52%. The percentage of drugs most commonly used inschizophrenia patients are typical antipsychotics 50.83% namely Trifluperazin 23.76%,Haloperidol 15.47, chlorpromazine 11.05%, Flufenazin 0.55% . The conclusion of the study isthat the use of the combination Triheksifenidil still causes Extrapyramidal in patients receivingtypical antipsychotics.